Apakah Penerapan Desentralisasi Memberikan Dampak yang tidak Baik? Studi Permukiman Kumuh di Jabodetabek - Husna, Meila; Yudhistira, Muhammad Halley (Jurnal Kebijakan Ekonomi, 2022)
The implementation of decentralization should have a positive impact on regional progress. Since its implementation in 2001, decentralization in Indonesia has become deeper and wider. Using the slum settlement policy as a study approach, this study will examine the impact of decentralization and how persistent these impacts are. The estimation results using RD-DiD shows that the implementation of decentralization has a negative correlation with the arrangement of slums in the Jabodetabek area. The area of slums is 45% greater than the year before decentralization or a non-decentralized area. Thus, in the aspect of structuring the slums, it can be concluded that decentralization does not work effectively and even tends to make things worse.